Case report: Image guidance retrieval of a foreign body in retropharyngeal space - Wu, Xingmei; Wang, Yongquan; Sun, Wei; Zhu, Xiaolin (Frontiers in Surgery, 2022)
Background Ingested foreign bodies fully embedded in retropharyngeal space present a unique challenge, as they can be difficult to locate and visualize via classic transoral laryngoscopy or the transcervical approach. Methods We retrieved a complete extraluminal chicken bone located in the patient's retropharyngeal space at the level of the C4-C5 spine through a well-designed transcervical approach with a combination of image-guided neck navigation. Conclusion A combined use of image-guided neck navigation and a dedicated transcervical approach for location of a foreign body in the retropharyngeal space is practical and available for clinical application.